Efeito do capeamento de apatita de araxá com alumínio sobre a disponibilidade de fósforo e o crescimento de planta - R., IVAN E. J. FERNANDEZ; NOVAES, ROBERTO F. DE; V., VICTOR HUGO ALVAREZ; FONTES, MAURÍCIO P. F.; RIBEIRO, ANTONIO C. (Revista Ceres, 2015)
.